Pengetahuan Arsiparis dalam Mengelola Arsip Dinamis Inaktif di Universitas Negeri Padang - Syuara, Khalid; Ardoni, Ardoni (Departemen Informasi Perpustakaan dan Kearasipan, 2025)
This study aims to describe the knowledge of archivists in managing inactive dynamic records at the State University of Padang, focusing on their understanding of inactive dynamic records and the records lifecycle. The research method used is descriptive qualitative with purposive sampling for data collection. Data analysis is conducted through three stages: data reduction, data presentation, and conclusion drawing. The results indicate a gap between theory and archivists' knowledge, particularly in understanding the concept of inactive dynamic records and its management principles. Archivists exhibit varying levels of understanding regarding the definition and characteristics of inactive dynamic records, as well as the application of centralization and decentralization principles in records management. Additionally, their understanding of the records lifecycle and maintenance procedures does not fully align with existing theories, potentially causing inefficiencies in records management. These findings underscore the importance of enhancing archivists' understanding through training and aligning records management practices with applicable archival standards.